51st Winter School on Wave and Quantum Acoustics Lth Winter School on Environmental Acoustics and Vibroacoustics Szczyrk, Poland, February 27 – March 3, 2023 - and Quantum Acoustics Lth Winter School on Environmental Acoustics; Vibroacoustics, 51st Winter School on Wave (Archives of Acoustics, 2023)
On behalf of the Upper Silesian Division of the Polish Acoustical Society (the main organizer) and the Committee of Acoustics of the Polish Academy of Sciences (the co-organizer) we are pleased to announce that after many years of tradition, the abovementioned Conferences known as the “Winter Schools” have been organized and completed with success. This year we were celebrating the Lth Winter School on Environmental Acoustics and Vibroacoustics, a conference well-known among Polish acousticians. For this reason, the “Winter Schools” began with a special, joined session dedicated to the celebration of this jubilee. As it has always been over the past 50 years of the conference history, Lth Winter School on Environmental Acoustics and Vibroacoustics was concerned with all environmental and vibroacoustics fields, but particularly with the traffic noise, vibroacoustics of machines, room acoustics, building acoustics, noise protection and similar problems. Many persons well-known from previous editions of the Conference joined us, either on-site or on-line. During the Conference, a seminar on “Industrial and Impulsive Noise” was organized in association with SVANTEK, which attracted 30 participants. 51st Winter School on Wave and Quantum Acoustics constituted platforms for sharing the results and achievements obtained in different branches of physical acoustics, as molecular acoustics, quantum acoustics, acousto-optics, magnetoacoustics, photoacoustics, acoustics of solid state, acoustic emission, and others. Moreover, researches in some selected topics related to those mentioned above (e.g., optoelectronics, relaxation processes) were presented during the school. The Conference consisted of the 18th Workshop on Acoustoelectronics and the 18th Workshop on Molecular Acoustics, Relaxation and Calorimetric Methods. However, the organizers are opened to organizing workshops on other subjects in the future. We would like to invite scientific centers and other professional groups to cooperate in organizing workshops on the subjects of their interests. In summary, 51 persons participated in the Conferences and seminars, presenting 46 lectures, reports, and posters. In this issue, one can find abstracts of some lectures and posters, which were presented during the Conferences. Further information about Conferences is available on our website: https://ogpta.pl/index.php/en/.